Trends, Patient Outcomes, and Resource Utilization Associated with Surgical Staplers During Robotic Sleeve Gastrectomy - Pan IW; Siddiqui ZA (ClinicoEconomics and Outcomes Research)
I-Wen Pan, Zasim Azhar Siddiqui Medtronic PLC, Boston, MA, USACorrespondence: I-Wen Pan, Medtronic PLC, 266 Summer St, 5th Floor, Boston, MA, 02110, USA, Email iwen.pan@gmail.comPurpose: Robotic platforms are commonly used for sleeve gastrectomy, despite the high capital costs and little understanding of the roles of platform-specific consumables and standard surgical alternatives in clinical outcomes and healthcare resource utilization. This study evaluates the trend, the effectiveness (outcomes) and efficiency (resource utilization) of different types of surgical staplers used in robotic sleeve gastrectomy (RSG).Patients and Methods: This was a retrospective observational cohort study analyzing data from the PINC AI™ Healthcare Data database. Patients were included if they underwent elective, inpatient, primary sleeve gastrectomy performed using the Intuitive Surgical robotic system (Sunnyvale, CA) with either a bedside stapler (BS, Signia™, Endo-GIA™, or Tri-staple™) or a robotic stapler (RS, Sureform™). The primary outcome measures included inpatient costs, complications, operating room time (ORT), length of stay (LOS), and intensive care unit visits. Outcomes were analyzed using bivariate analyses, multivariable generalized linear models (GLM), and propensity-score matching (PSM).Results: Of 18,892 total RSG procedures that met eligibility criteria, robotic staplers were used in 15,152 procedures (80.2%) and bedside staplers were used in 3740 (19.8%). While RSG increased dramatically during the period, RS were shown to be associated with a greater risk of blood transfusion compared to bedside staplers both in a GLM [0.5% (BS) vs 0.7% (RS); Odds ratio (OR): 1.55; 95% confidence interval (CI): 1.02– 2.36; p = 0.04] and after PSM [0.3% (BS) vs 0.9% (RS); OR: 3.02; 95% CI: 1.35– 6.73; p = 0.007]. Bedside staplers were associated with total costs reduction [mean cost savings: $3084; 95% CI: $2860 - $3309; p < 0.001] and shorter ORT (21 minutes; 95% CI: 18.6– 23.5; p < 0.001) compared to robotic staplers. Difference in LOS was not clinically significant.Conclusion: When used during RSG, bedside staplers are cost-saving, with equivalent or better clinical outcomes and reduced resource utilization compared to robotic staplers.Plain Language Summary: Robotic sleeve gastrectomy (RSG) is a type of weight loss surgery that involves reducing the stomach size using surgical staples. Robotic systems are becoming increasingly popular for this surgery and physicians often use staplers that are integrated and sold with robotic surgery systems. However, surgeons can also use an alternative - the standard “bedside” stapler. In this study, we evaluate whether the type of stapler used affects patient outcomes or costs.We analyzed data from over 18,000 individuals who underwent RSG between 2018 and 2022. Robotic staplers were used in 80.2% of these surgeries, while bedside staplers were used in 19.8% of surgeries. We found that patients who used robotic staplers had a higher chance of needing a blood transfusion, while using bedside staplers saved inpatient costs and shortened surgery time. These findings suggest that bedside staplers offer a safe and more cost-effective option for RSG.Keywords: bariatric surgery, robotic surgery, healthcare costs and resource utilization